Clinical Pharmacy 2017
DOI: 10.1136/ejhpharm-2017-000640.85
|View full text |Cite
|
Sign up to set email alerts
|

CP-086 CD69 A>G (RS11052877) genetic polymorphism on the response to tocilizumab in rheumatoid arthritis patients

Abstract: BackgroundCD69 receptor is a C lectin transmembrane protein expressed by T cells, natural killer (NK) cells and active B cells. This receptor is involved in the production and regulation of T cells, B cells and NK cells, and these are involved in interleukin 6 (IL-6) production. IL-6 is a multifunctional glycoprotein involved in the immune response, inflammation and bone metabolism; IL-6 makes significant contributions to autoimmune and inflammatory diseases such as rheumatoid arthritis (RA). Tocilizumab is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Relationship between CD69 rs11052877 A alleles and good tocilizumab response was further validated in a study with 79 RA patients enrolled ( 300 ). In contrast, another study concluded that CD69 rs11052877 A/G genetic polymorphism was not useful as a predictor of tocilizumab response in RA patients ( 340 ). Data from 87 patients suggested that FCGR3A rs396991-TT could be used to predict better EULAR response ( 286 ).…”
Section: Bdmards Blocking T Cells Cd20 and Il-6rmentioning
confidence: 99%
“…Relationship between CD69 rs11052877 A alleles and good tocilizumab response was further validated in a study with 79 RA patients enrolled ( 300 ). In contrast, another study concluded that CD69 rs11052877 A/G genetic polymorphism was not useful as a predictor of tocilizumab response in RA patients ( 340 ). Data from 87 patients suggested that FCGR3A rs396991-TT could be used to predict better EULAR response ( 286 ).…”
Section: Bdmards Blocking T Cells Cd20 and Il-6rmentioning
confidence: 99%